Far in the waste Sudan : on assignment in Africa - Coghlan, Nicholas, 1954- (McGill-Queen's University Press, 2005)
In 2000, with controversy raging over the presence in Sudan of Talisman Energy, Canada's largest independent oil and gas producer, Ottawa decided to open a post in Khartoum. Nicholas Coghlan was recalled from assignment in Colombia to set up and run Canada's first diplomatic post in the largest country in Africa. "In diplomatic circles, you cry when you hear you've been posted to Sudan," says Coghlan. "But you cry even more when you leave." Far in the Waste Sudan weaves together a personal and political account of Coghlan's three-year appointment